Penambahan Bunga Marigold (Tagetes Erecta L.) Sebagai Antioksidan Alami untuk Memperlambat Tingkat Ketengikan Virgin Coconut Oil - Ni Made Suaniti; Ni Nyoman Nadia Angela Kusuma P.; Oka Ratnayani (Publikasi Indonesia, 2023)
Virgin Coconut Oil or VCO will experience a decrease in quality due to oxidation, which cause rancidity. Adding antioxidants to VCO can help slow down the rancidity of the oil. This study aimed to determine the effect of adding marigold flowers on VCO in terms of free fatty acids (FFA) and water content as well as the functional groups contained in VCO. The VCO preparation technique was carried out without heating followed by the addition of marigold flowers with a ratio of VCO and marigold flowers of 100:1; 100:2.5; 100:5 w/w. The VCO without the addition of marigold flowers used as a control. The results indicated that the addition of marigold flowers could improve the quality of the VCO, characterized by a decrease in FFA levels and water content. The functional groups of VCO with the best quality (a ratio of VCO and marigold flowers of 100:1) were analyzed by FTIR (Fourier Transform Infrared Spectroscopy), namely OH, CH¬3, C=O, aliphatic C=C, and aliphatic C?C.